Oficina de curadoria para o ensino de línguas estrangeiras - MONTEIRO, Eliene Botelho (Universidade Federal do Pará, 2023)
This research entitled Applications curation workshop for the teaching of foreign languages consisted in the development of an educational product resulting from a workshop given to undergraduate students in English Language and Literature from Faculdade de Letras Estrangeiras Modernas (FALEM), at Federal University of Pará (UFPA) – Belém campus, studying the subject Technologies in the Teaching/Learning of Foreign Languages. The Workshop consisted of six stages, which were later validated by a Panel of Experts. This Panel comprised two teachers trained in the area of teaching and learning English, training teachers of English and technologies in teaching and learning in the target language. The research was based on studies of digital curation in the educational context (NESBIT, BELFER, LEACOCK, 2009; CORRÊA, BERTOCCHI, 2012; RAMOS, 2012; SILVA, 2012; CASTILHO, 2015; DESCHAINE, SHARMA, 2015; among others); technologies in the teaching and learning of foreign languages, citing the works of Gardner and Davis (2014), Chen (2016), Nunes e Bergmann (2019), Araújo (2020), Al-Sarf (2020), Scheifer and Rego (2020), Policarpo, Nunes e Bergmann (2020), among other authors; and in digital competences from the recommendations of the Council of the European Union (2018), specifically, the competences arising from The European Framework for Digital Competence of Educators (DIGCOMPEDU), prepared by Redeker and Punie (2017). To analyze the data generated from the educational product, qualitative and quantitative approaches were used, following the principles of action research. The results reveal that it is possible to use applications that were not designed for educational purposes from theoretical-practical discussions on the themes of curation of digital educational resources, mobile learning, and authentic material, followed by an application evaluation matrix and planning of activities classes. Furthermore, the results also point to the need to expand reflective and critical discussions for the selection and evaluation process of curatorship of digital educational resources in initial foreign languages training courses.